Characterization Of Ilmenite Ore Samples From Dankoli In North Western Nigeria - Adelana Adetunji (The Minerals, Metals and Materials Society, 2006)
Ilmenite ore samples obtained from Dankoli in Zamfara, North Western Nigeria has been characterized using Energy Dispersive X-ray fluorescence (EDXRF) technique, X-ray diffraction (XRD) technique and the Neutron Activation Analysis (NAA) technique. The major constituents in the ore were quantitatively found to be TiO2 and Fe2O3 in concentrations of about 60wt% and 31wt% respectively. These occur in the forms of magnesian ilmenite (Fe, Mg)(Ti, Fe)O3, pure ilmenite (FeTiO3), and barium copper yttrium oxide (Ba2Cu3YO6.56) minerals. Other constituents/impurities in minor or trace quantities include MnO, Ta2O5, Nb2O5, Wo, SnO2, Hf, Zn, V, Zr, Co, Pb, Br, Al, Rb, Y, Th and U.